Inhibition of RNA-binding protein HuR reduces glomerulosclerosis in experimental nephritis. Issue 12 (18th June 2020) - Liu, Simeng; Huang, Zhimin; Tang, Anna; Wu, Xiaoqing; Aube, Jeffrey; Xu, Liang; Xing, Changying; Huang, Yufeng
Abstract: Recent identification of an RNA-binding protein (HuR) that regulates mRNA turnover and translation of numerous transcripts via binding to an ARE in their 3′-UTR involved in inflammation and is abnormally elevated in varied kidney diseases offers a novel target for the treatment of renal inflammation and subsequent fibrosis. Thus, we hypothesized that treatment with a selective inhibition of HuR function with a small molecule, KH-3, would down-regulate HuR-targeted proinflammatory transcripts thereby improving glomerulosclerosis in experimental nephritis, where glomerular cellular HuR is elevated. Three experimental groups included normal and diseased rats treated with or without KH-3. Disease was induced by the monoclonal anti-Thy 1.1 antibody. KH-3 was given via daily intraperitoneal injection from day 1 after disease induction to day 5 at the dose of 50 mg/kg BW/day. At day 6, diseased animals treated with KH-3 showed significant reduction in glomerular HuR levels, proteinuria, podocyte injury determined by ameliorated podocyte loss and podocin expression, glomerular staining for periodic acid-Schiff positive extracellular matrix proteins, fibronectin and collagen IV and mRNA and protein levels of profibrotic markers, compared with untreated disease rats. KH-3 treatment also reduced disease-induced increases in renal TGFβ1 and PAI-1 transcripts. Additionally, a marked increase in renal NF-κB-p65, Nox4, and glomerular macrophage cell infiltration observed in disease control group was largely reversed by KH-3 treatment. These results strongly support our hypothesis that down-regulation of HuR function with KH-3 has therapeutic potential for reversing glomerulosclerosis by reducing abundance of pro-inflammatory transcripts and related inflammation.